2009
DOI: 10.1038/onc.2009.230
|View full text |Cite
|
Sign up to set email alerts
|

Functional interaction of HTLV-1 Tax protein with the POZ domain of the transcriptional repressor BCL6

Abstract: The Tax protein encoded by human T-cell leukaemia virus type 1 (HTLV-1) has a pivotal role in T-cell transformation by deregulating cellular signalling pathways. Using the yeast two-hybrid system to screen a human leukocyte cDNA library, we identified BCL6 (B-cell lymphoma 6) as a cellular protein, which interacts with Tax 1. The BCL6 gene encodes a sequence-specific transcriptional repressor that contains a conserved N-terminal poxvirus and zinc finger (POZ) repressor domain and a C-terminal Kruppel-like zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…This supported by the findings in previous study [52], which described that an interaction of Tax with the POZ domain of BCL6 enhances the repressive activity of BCL6 and increased the levels of apoptosis induced by BCL6 in osteosarcoma cells. The BCL6 POZ domain mediates transcriptional repression by interacting with several corepressors including silencing mediator for retinoid and thyroid receptor and nuclear hormone receptor corepressor, BCL6 corepressor together with many histone deacetylases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This supported by the findings in previous study [52], which described that an interaction of Tax with the POZ domain of BCL6 enhances the repressive activity of BCL6 and increased the levels of apoptosis induced by BCL6 in osteosarcoma cells. The BCL6 POZ domain mediates transcriptional repression by interacting with several corepressors including silencing mediator for retinoid and thyroid receptor and nuclear hormone receptor corepressor, BCL6 corepressor together with many histone deacetylases.…”
Section: Discussionsupporting
confidence: 91%
“…BCL6 colocalizes with these corepressors in punctate nuclear structures that have been identified as sites of ongoing DNA replication. Interestingly, BCL6 appeared to recruite Tax into punctate nuclear structures and significantly downregulate both basal and Tax-induced NF-kB and long terminal repeat activation [52]. Thus, the high expression of BCL6 in HTLV infected cells may contribute to the silencing of viral gene expression and to the long clinical latency associated with HTLV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Greco et al [5] showed that accumulation of fatty acid in liver was closely related to hepatocellular injury, and Feldstein et al [30] speculated that hepatocyte apoptosis might be the early pathological change before hepatocellular injury, inflammation and necrosis in high-fat diet-induced NAFLD. The present study found that several genes playing pivotal roles in inducing cell apoptosis, including bcl6 [31], cdkn1a, tgfb1 [32] and foxl2 [33], were augmented in expression, while dusp1 [34] participating in anti-apoptosis by inactivating MAPK was down-regulated. In addition, the marker genes for apoptosis, casp3 and casp8, were increased with the development of NAFLD, and reached their peaks in the sixth week.…”
Section: Discussionmentioning
confidence: 83%
“…Other, less characterized, points of interaction by the AHR include Irf8, Xbp1, and Myc, which have been identified as potential direct transcriptional targets of the AHR in B cells using ChIP-on-chip and time course microarray analysis (De Abrew et al , 2010). Irf8 transcriptionally activates Bcl6 (Lee et al , 2006; Ku et al , 2008) and Xbp1 transcriptionally upregulates Tax1 (Ku et al , 2008) which, in turn, physically interacts with Bcl6 to enhance its repressive activity (Dean et al , 2009). Myc has been predicted to transcriptionally regulate Irf4 (Chen et al , 2007), which is a transcriptional activator of Prdm1 (Calame, 2008).…”
Section: Discussionmentioning
confidence: 99%